Edukasi Cegah Stunting pada Warga RT 02 RW 06 Rumbai Timur Kota Pekanbaru - Nita, Yureya; Puswati, Desti; Devita, Yeni; Ezalina, Ezalina; Fa'izah, Nurul; Husaila, Husaila (Jurnal Abdimas Kesehatan (JAK), 2025)
Stunting is a problem that is increasingly found in developing countries, including Indonesia. Stunting occurs due to the problem of nutritional intake received during pregnancy, infantry and childhood. Mother's ignorance about health and nutrition before and after pregnancy. The purpose of this community service is that stunting is a disorder of child growth and development caused by lack of nutritional intake, infection, and inadequate stimulation. This community service activity was carried out with a health counseling method by providing education to residents in East Rumbai RT 02, RW 06, Pekanbaru City, Riau. The time for the implementation of the service is in June 2024. Participants in community service activities to prevent stunting in children are residents in RT 02/RW06, East Rumbai District, Pekanbaru City, Riau. The number of participants who took part in this activity was 25 people with an age range of 25 – 45 years. The result of this health counseling is that most of the participants can understand the material well. This is evidenced by the number of people who ask enthusiastically to get knowledge and information related to stunting. The results of the pre-test evaluation were 63%, and after health counseling, the results of the participants' post test became 92%. With the holding of this activity, the residents of East Rumbai should understand more about stunting prevention, and it will be beneficial in the future for residents who will have children, and who already have children. Advice for East Rumbai residents is expected to be able to apply new knowledge by consuming good food and drinks to maintain and avoid stunting after getting education related to stunting prevention.